Biochemical and behavioral indices related to BMI in schoolchildren in urban Turkey - (:unkn) unknown (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2005)
Background. The aim of the current study was to examine the interrelationship between certain cardiovascular disease (CVD) risk factors and overweight, as well as to provide some indication on the prevalence of underweight, overweight and obesity in primary schoolchildren in urban Turkey. Methods. 1044 randomly selected children aged 12 and 13 years old from the urban areas of Istanbul. Ankara and Izmir were examined. The main variables of interest were fatness determined by body mass index and slim of skinfolds. lipid profile, dietary intake, physical fitness and habitual physical activity. Results. Both overweight boys and girls were found to have lower cardiovascular fitness levels compared to their normal weight peers. Overweight boys reported lower energy and macronutrient intake than their normal weight counterparts. Regarding biochemical indices, overweight boys were found to have higher total cholesterol (TC), Low Density Lipoprotein-cholesterol (LDL-C), triglycerides (TG) and LDL-C/HDL-C ratio compared to normal weight boys, while overweight girls were found to have lower High Density Lipoprotein-cholesterol (HDL-C) and higher TG compared to their normal weight peers. Finally, the prevalence or underweight. overweight and obesity for the overall population was found to be 12%, 12% and 2%, respectively. Conclusions. The study revealed that overweight and obesity in children coexisted with more unfavorable lipid profiles and lower cardiovascular fitness levels. This finding points out the emergent need for suitable measures, to be implemented in order to identify and counteract these health and social problems early in life. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: cross-sectional study; cardiovascular disease risk factors; diet and exercise; physical fitness; underreporting; PHYSICAL-ACTIVITY; NUTRITIONAL-STATUS; BODY-COMPOSITION; ENERGY-INTAKE; RISK-FACTORS; CHILDHOOD OBESITY; CHILDREN; OVERWEIGHT; FITNESS; ADOLESCENTS